PERBANDINGAN METODE KATO – KATZ DENGAN METODE STOLL UNTUK PEMERIKSAAN TELUR CACING SOIL TRANSMITTED HELMINTH PADA SAMPEL FESES - Octania nugraha, Hanayori; Sulaeman; Sundara, Yuliansyah; Kurniawan, Entuy (Politeknik Kesehatan Kemenkes Bandung, 2024)
Soil transmitted helminth (STH) is a group of intestinal parasitic worms of the nematode class that can cause human infection through soil contaminated with their eggs or larvae. Soil transmitted helminth types that most commonly infect humans are Ascaris lumbricoides (A. lumbricoides), Trichuris trichiura (T. trichiura) and hookworms (Necator americanus (N. americanus) and Ancylostoma duodenale (A. duodenale). The intended purpose of this study is to determine the similarity of worm egg identification results between the Kato-Katz and the Stoll method. The statistical analysis applied in this study is Paired T test. The results of this study showed that the Kato-Katz and Stoll methods applied to five feces samples indicated Soil Transmitted Helminth (STH) worms in the laboratory of the Poltekkes Kemenkes Bandung found the presence of the two most common types of worm eggs; Ascaris lumbricoides and Trichuris trichiura. Meanwhile, hookworm eggs were not found in the two methods. It was found that the number of Ascaris lumbricoides eggs was more when compared to Trichuris trichiura. Statistical data identified that both methods had a normal distribution (Shapiro-Wilk test) with a difference (Paired T_test, p=0.024). Where the most eggs were found in the Kato-Katz method. The Kato-Katz and Stoll methods for Trichuris trichiura had a correlation (r=0.893, p=0.0001). The sensitivity of these two methods is 100%, but the specificity cannot be calculated because all samples were positive for STH. Therefore, WHO recommends the Kato-Katz method in the examination of STH infection because it is superior in the detection of worm eggs.